Shareholder wealth effects and bid negotiation in freeze-out deals: Are minority shareholders left out in the cold? - Bates, Thomas W.; Lemmon, Michael L.; Linck, James S. (Journal of Financial Economics, 2006)
This paper examines the shareholder wealth effects of bids by controlling shareholders seeking to acquire the remaining minority equity stake in a firm, deals commonly referred to as minority freeze-outs. Minority claimants in freeze-out offers receive an allocation of deal surplus at the bid announcement that exceeds their pro rata claim on the firm. An analysis of bid outcomes and renegotiation indicates that minority claimants and their agents exercise significant bargaining power during freeze-out proposals. Overall, our results suggest that legal standards and economic incentives are sufficient to deter self-dealing by controllers during freeze-out bids.